التنافسية الإقليمية الحضرية المستدامة في المحافظات السورية (منهجية قياسها وسياسات تحقيقها) - ميّا, رولا; فاخوري, رهام (Latakia University Journal -Engineering Sciences Series, 2016)
أصبحت التنافسية اليوم واحدة من أهمّ استراتيجيات التنمية المكانية؛ باعتبارها أداة من أدوات التنمية الإقليمية ذات تأثير مكاني مباشر وسريع على التنمية الاقتصادية والاجتماعية وحتى البيئية، وتبذل الدول ما بوسعها على مستوى عالمي أو حتى على مستوى إقليمي داخلي بأن ترتقي بسوية تنافسيتها وتحسّن مستوى شعوبها، ولكن تلك الأداة غير كافية؛ إذ يجب أن تترافق مع أدوات وآليات أخرى ومن ضمنها مجموعة من السياسات التي تدعم التنافسية بين الأقاليم من خلال استثمار مواردها وإمكانياتها الموجودة بشكلٍ حضاريٍ مستدامٍ. وفي ضوء ما سبق؛ يدرس البحث موضوع التنافسية من وجهة نظر عمرانية تخطيطية، ويحلِّل عواملها المختلفة وارتباطها بموضوع التنمية المستدامة، كما يدرس البحث ويحلِّل مؤشرات التنافسية الحضرية التي تتَّبعها الدول العالمية التي تحوي المدن والأقاليم الأكثر تنافسية، ويتوصّل إلى مجموعة مؤشرات خاصة يمكن أن تُطبَّق في المدن والأقاليم العربية ومن ضمنها أقاليم الجمهورية العربية السورية بما تشمله من محافظات بشكلٍ يجعلها تندمج مع التطور العالمي، وفي النهاية يضع البحث مجموعة من السياسات القادرة على تحسين تنافسية الأقاليم والمحافظات السورية وتحقيق تنمية محلية ووطنية مستدامة. Competitiveness nowadays becomes one of the most important strategies for spatial development, and it is considered as a tool of quick and direct regional development impact on the economic, social and environmental development. According to that, states do what they can on a global level or even on a regional level in order to elevate the development level for its cities and improve the Standards of living for their people too. But this tool is not sufficient by itself; it should be accompanied by other instruments such as setting and applying a group of policies that can support the resources and potentials of the regions in a sustainable civilized Way. This research examines the subject of competitiveness from the perspective of urban planning and analyzes the different factors of Competitiveness and its relates to the sustainable development. The research also examines and analyzes the urban competitiveness indicators pursued by the global countries, in order to reach a group of specific indicators that can be applied in Syrian Provinces. Finally; the research puts a set of policies capable of improving the competitiveness of Syrian regions and provinces to improve the competitiveness level of the provinces and achieve a well local and national sustainable development.